2015
DOI: 10.1038/ncomms10204
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic switch drives the conversion of fibroblasts into proinvasive cancer-associated fibroblasts

Abstract: Carcinoma-associated fibroblasts (CAF) mediate the onset of a proinvasive tumour microenvironment. The proinflammatory cytokine LIF reprograms fibroblasts into a proinvasive phenotype, which promotes extracellular matrix remodelling and collective invasion of cancer cells. Here we unveil that exposure to LIF initiates an epigenetic switch leading to the constitutive activation of JAK1/STAT3 signalling, which results in sustained proinvasive activity of CAF. Mechanistically, p300-histone acetyltransferase acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
264
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(279 citation statements)
references
References 62 publications
4
264
0
2
Order By: Relevance
“…Acetylation-dependent gene induction has been shown to play a pivotal role in the progression of cancer invasion, metastasis, and kidney fibrosis. [47][48][49] We previously reported that the excessive production of ROS induced epithelial-mesenchymal transition (EMT), which is considered to be critically involved in cancer metastasis and fibrosis and is mediated by histone acetylation in the human breast cancer cell line MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation-dependent gene induction has been shown to play a pivotal role in the progression of cancer invasion, metastasis, and kidney fibrosis. [47][48][49] We previously reported that the excessive production of ROS induced epithelial-mesenchymal transition (EMT), which is considered to be critically involved in cancer metastasis and fibrosis and is mediated by histone acetylation in the human breast cancer cell line MCF-7.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this epigenetic event coincides with elevated DNA methyltransferase 1 (DNMT1) activity and histone H3 Lys9 trimethylation (H3K9me3), supporting the occurrence of more frequent epigenetic events in CAFs. Another study demonstrated a pivotal role for the proinflammatory cytokine leukemia inhibitory factor (LIF) in epigenetic-driven activation of fibroblasts into CAFs via constitutive activation of the Janus kinase 1 (JAK1)/signal transducer and activator of transcription 3 (STAT3) pathway following STAT3 acetylation and up-regulation of DNMT1 and DNMT3b activities (Albrengues et al 2015). Combined inhibition of DNMT activities and JAK signaling results in long-term reversion of the CAF phenotype into a nonprotumorigenic fibroblast phenotype.…”
Section: Caf: Cell or State?mentioning
confidence: 99%
“…IHC of PDAC samples exhibited decreased SOCS1 expression in tumor-associated stroma compared with normal stroma areas of tissue, validating their finding in vivo. Finally, Albrengues et al [45] demonstrated that treatment of normal fibroblasts with leukemia inducible factor, an IL6 class cytokine secreted by cancer cells, causes hypermethylation and silencing of the SHP-1 tyrosine phosphatase gene, PTPN6. Silencing of gene causes constitutive activation of JAK1, thus promoting the fibroblast proinvasive phenotype [45].…”
Section: Evidence For Epigenetic Regulation In Stromal Cellsmentioning
confidence: 99%